2018
DOI: 10.1128/msystems.00206-18
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Human Milk Oligosaccharides and N-Glycans in the Milk of Chinese Mothers Regulate the Gut Microbiome of Their Breast-Fed Infants during Different Lactation Stages

Abstract: Human milk glycans provide a broad range of carbon sources for gut microbes in infants. Levels of protein glycosylation in human milk vary during lactation and may also be affected by the stages of gestation and lactation and by the secretor status of the mother. This was the first study to evaluate systematically dynamic changes in human milk oligosaccharides and fucosylated N-glycans in the milk of Chinese mothers with different secretor statuses during 6 months of lactation. Given the unique single nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 78 publications
13
101
3
Order By: Relevance
“…Nevertheless, these HMOs deeply decreased at 6 months. One study revealed that fucosylated HMOs could regulate the gut microbiome of infants during different lactation stages [27]. We believe that infants need to be exposed to a certain content of HMOs at specific stages of their development, and different pathways of HMOs exert different roles during different stages.…”
Section: Hmos Concentration During Lactationmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, these HMOs deeply decreased at 6 months. One study revealed that fucosylated HMOs could regulate the gut microbiome of infants during different lactation stages [27]. We believe that infants need to be exposed to a certain content of HMOs at specific stages of their development, and different pathways of HMOs exert different roles during different stages.…”
Section: Hmos Concentration During Lactationmentioning
confidence: 97%
“…However, most studies collected samples in a single time point or focused on first few weeks of lactation. In addition, HMOs vary during lactation and may also be influenced by the gestational stage [17,27]. Recently, researchers found that HMOs composition and concentration presented a wide variability in women with the same genetic background [28], which suggested that sociodemographic and environmental factors may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Among the complex N-glycans, we noticed that the glycans carrying one fucose gradually decreased, while those harboring multiple fucose moieties increased in time from early to mature lactation, again consistent with previous findings based on studies focused on released N-glycans. 22 Having established a global picture of the glycan distribution as occurring on glycoproteins in human milk, we used these data to make a rough comparison to the global distribution of glycans in human serum, taking serum data reported earlier 23 ( Figure S2). This comparison revealed, not surprisingly, that global glycoproteome compositions in human milk and serum are quite distinct.…”
Section: Journal Of Proteome Research Pubsacsorg/jpr Articlementioning
confidence: 99%
“…However, the question concerning which transferases contribute to HMO sialylation remains unanswered. Interestingly, the obtained structures, despite the small structural differences, namely the position of the glycosidic bond with identical qualitative composition for fucosyllactose and sialyllactose, respectively (Figure 1a), show significant functional differences in shaping the gut microbiome and in different levels of protection against fucose-or sialic acid-dependent pathogens, among others [19,32,[38][39][40][41][42][43]. The actions of different fucosyltransferases and sialyltransferases allow the identification of over 100 different oligosaccharide structures [21] Depending on the presence of fucose and sialic acid in the oligosaccharide structure, HMOs are divided as follows: fucosylated (neutral) and non-fucosylated (neutral) oligosaccharides and sialylated (acidic) and non-sialylated molecules, respectively.…”
Section: Structures and Diversity Of Hmosmentioning
confidence: 99%
“…Concentration and mutual proportions of HMOs are affected mainly by 3 different factors, namely polymorphisms of two fucosyltransferase genes (FUT2 and FUT3), which gives 4 different groups of mothers [20,45], stage of milk maturation [40,46] and the week of delivery [47,48]. [49][50][51].…”
Section: Structures and Diversity Of Hmosmentioning
confidence: 99%